A evolução dos direitos trabalhistas das mulheres sob à ótica da tutela jurídica de proteção à gravidez e à maternidade no direito do trabalho - CARDOSO, Tamara Soares (2024)
This study considers the evolution of women's labor rights from the perspective of legal protection for pregnancy and motherhood, addressing basic concepts of Labor Law. It then discusses the legal framework surrounding the institute of Maternity Leave, regulated by Federal Law No. 10,421, of April 15, 2002, which amended article 392 of the Consolidation of Labor Laws (CLT). The central issue of this work is to determine to what extent the legislation related to the protection of women during the pre and post-gestational period is sufficient to guarantee women's fundamental rights in the labor market. In other words, this study seeks to verify whether the existing regulations effectively protect women or, on the contrary, exacerbate their discrimination in the labor market. To this end, the methodology used includes bibliographic research, jurisprudence, and legislation. The scope is defined as addressing the acquired rights of women during the pre and post-gestational period, seeking to understand the motivations that led to the establishment of specific regulations for women and the controversies surrounding this regulation. As a result, a significant reduction in disparities between men and women in the labor market was found. However, we are still far from the much-desired gender equality guaranteed by the Constitution, highlighting that many changes need to be studied and applied in Brazil to reduce the discrepancy between men and women in the labor market and to ensure the safety of pregnant working women.